Interaction of HLA and age on levels of antibody to plasmodium falciparum rhoptry-associated proteins 1 and 2 - Johnson, A.; Leke, R.; Harun, L.; Ginsberg, C.; Ngogang, J.; Stowers, A.; Quakyi, I.A. (Infection and Immunity, 2000)
The Plasmodium falciparum rhoptry-associated proteins 1 and 2 (RAP1 and RAP2) are candidate antigens for a subunit malaria vaccine. The design of the study, which looks at the acquisition of immunity to malaria from childhood to old age, has allowed us to document the interaction of HLA and age on levels of antibody to specific malarial antigens. Antibodies reach maximum levels to RAP1 after the age of 15 but to RAP2 only after the age of 30. The effect of HLA-DRB1 and -DQB1 and age on levels of antibody to rRAP1 and rRAP2 was analyzed with a multiple regression model in which all HLA alleles and age were independent variables. DQB1*0301 and -*03032 showed an age- dependent association with levels of antibody to rRAP1, being significant in children 5 to 15 years (P < 0.001) but not in individuals over 15 years of age. DRB1*03011 showed an age-dependent association with antibody levels to rRAP2; however, this association was in adults over the age of 30 years (P < 0.01) but not in individuals under the age of 30 years. No associations were detected between DRB1 alleles and RAP1 antibody levels or between DQB1 alleles and RAP2 antibody levels. Thus, not only the HLA allele but also the age at which an interaction is manifested varies for different malarial antigens. The interaction may influence either the rate of acquisition of antibody or the final level of antibody acquired by adults.
Keywords: EMTREE medical terms: allele; antibody response; antibody titer; antigen specificity; article; complex formation; cross reaction; HLA system; nonhuman; parasitemia; passive immunization; Plasmodium falciparum; priority journal; protein protein interaction; regression analysis; MeSH: Adolescent; Adult; Age Factors; Aged; Alleles; Animals; Antibodies, Protozoan; Child; Child, Preschool; Enzyme-Linked Immunosorbent Assay; Hemoglobin, Sickle; HLA-DQ Antigens; HLA-DR Antigens; Humans; Immunity; Malaria, Falciparum; Middle Aged; Plasmodium falciparum; Polymorphism, Genetic; Protozoan Proteins; Recombinant Proteins